Topographically and Chemically Modified Surfaces for Expansion or Differentiation of Embryonic Stem Cells - Markert, Lotte D’Andrea; Lovmand, Jette; Duch, Mogens; Pedersen, Finn Skou (IntechOpen, 2011)
None